Vascular and metabolic response to statin in the mildly hypertensive hypercholesterolemic elderly (Clinics, 2008)
INTRODUCTION: Much evidence indicates the importance of the endothelium and hypercholesterolemia in atherosclerosis, as well as the decline in endothelial function with aging. However, it is unclear if treating dyslipidemia in elderly patients improves endothelial function and reduces C-reactive protein levels. OBJECTIVES: To evaluate vasomotor function, lipids and C-reactive protein in mildly hypertensive and hypercholesterolemic elderly patients treated with atorvastatin. METHODS: Forty-seven elderly Brazilian subjects (>; 65 years old) with LDL cholesterol (LDL-c) >; 130 mg/dL were randomly assigned, in a double-blinded manner, to receive either placebo (n = 23) or 20 mg/day of atorvastatin (n = 24) for 4 weeks. Exclusion criteria included diabetes, serious hypertension, obesity, steroid use, hormone replacement, and statin use within the previous six months. All patients underwent clinical examinations, laboratory tests (glucose, lipids, liver enzymes, creatine phosphokinase and high sensitivity C-reactive protein) and assessment of vasomotor function by high-resolution ultrasound examination of the brachial artery (flow-mediated dilation and sublingual nitrate), both before and after treatment. RESULTS: The patients were 65 to 91 years old; there was no significant difference between basal flow-mediated dilation of placebo (7.3 ± 6.1%) and atorvastatin (4.5 ± 5.1%; p = 0.20). The same was observed after treatment (6.6 ± 6.2 vs. 5.0 ± 5.6; p = 0.55). The initial nitrate dilatation (8.1 ± 5.4% vs. 10.8 ± 7.5%; p = 0.24) and that after 4 week treatment (7.1 ± 4.7% vs. 8.6 ± 5.0%; p = 0.37) were similar. Atorvastatin produced a reduction of 20% of the C-reactive protein and 42% in the LDL-c; however, there were no changes in the flow-mediated dilation. CONCLUSIONS: Atorvastatin produced a significant change of lipids and C-reactive protein; however, there were no changes in vasomotor function, suggesting the existence of intrinsic age-related vessel alterations.